Hepatic-Modulatory Effects of Chicken Liver Hydrolysate-Based Supplement on Autophagy Regulation against Liver Fibrogenesis - Yi-Ling Lin; Chih-Ying Chen; Deng-Jye Yang; Yi-Hsieng Samuel Wu; Yue-Jia Lee; Yi-Chou Chen; Yi-Chen Chen (Antioxidants, 2023)
Chicken-liver hydrolysates (CLHs) have been characterized as performing several biofunctions by our team. This study aimed to investigate if a CLH-based supplement (GBHP01TM) can ameliorate liver fibrogenesis induced by thioacetamide (TAA) treatment. Our results showed that the TAA treatment caused lower body weight gains and enlarged livers, as well as higher serum ALT, AST, and ALP levels (p < 0.05). This liver inflammatory and fibrotic evidence was ameliorated (p < 0.05) by supplementing with GBHP01TM; this partially resulted from its antioxidant abilities, including decreased TBARS values but increased TEAC levels, reduced GSH contents and catalase/GPx activities in the livers of TAA-treated rats (p < 0.05). Additionally, fewer nodules were observed in the appearance of the livers of TAA-treated rats after supplementing with GBHP01TM. Similarly, supplementing GBHP01TM decreased fibrotic scars and the fibrotic score in the livers of TAA-treated rats (p < 0.05). Moreover, the increased hepatic IL-6, IL-1β, and TNF-α levels after TAA treatment were also alleviated by supplementing with GBHP01TM (p < 0.05). Meanwhile, GBHP01TM could decrease the ratio of LC3B II/LC3B I, but upregulated P62 and Rab7 in the livers of TAA-treated rats (p < 0.05). Taking these results together, the CLH-based supplement (GBHP01TM) can be characterized as a natural agent against liver fibrogenesis.